Reimagining City Identities in Globalisation: A Constructivist Study on City Paradiplomacy - Ario Bimo Utomo (Institute of International Studies, 2019)
The study of diplomacy has encountered a new turn when the concept of parallel diplomacy, or paradiplomacy, was introduced to the mainstream. The concept itself can be defined as the international agency of sub-national political entities. The logic behind this is that globalisation has given a channel for the local entities to further their interests amidst the prevailing state-centric international system. In the International Relations scholarship, this issue can be viewed through three lenses: realist, liberalist, and constructivist. This article will use constructivism whose idea argues that paradiplomacy contains identity-seeking undertones beneath, where sub-national entities can reimagine their positions in globalisation. The constructivist lens offers more advantage in seeing paradiplomacy beyond activities which are mainly driven by free-trade. This paper attempts to use the constructivist lens of paradiplomacy in exploring how cities can construct their identities in globalisation. There has been a quite extensive literature on constructivist perspective on paradiplomacy, yet many of them are focused on secessionist case studies instead of cities as regular sub-national units which pose no threat to their host states. This article argues that identity creation in city paradiplomacy is possible and particularly essential to cities located in developing countries seeking partnerships with the more developed regions. In doing the research, the author utilises secondary sources through the existing studies on paradiplomacy and city identity in globalisation to keep up with the current state of the art.